Pemenuhan nafkah bagi anak yatim dalam perspektif hukum Islam - Faizah, Nur (AS-SAKINAH, 2024)
The practice of fulfilling maintenance for orphans is an important aspect of Islamic law, which bases its principles on the welfare and protection of children's rights. This article discusses the perspective of Islamic law regarding the fulfillment of orphan maintenance, exploring the legal principles that regulate rights and obligations in this regard. The analysis covers the obligations of parents or guardians, and the inherent rights of orphans in the context of meeting basic needs, education, and psychosocial well-being. The article also reviews some contemporary practices in the fulfillment of orphan maintenance, highlighting issues that may arise and efforts to improve the child protection system within the framework of Islamic law. Considering humanitarian values and social justice, this study proposes solutions that can improve the effectiveness of the fulfillment of orphan maintenance under the teachings of Islamic law.